Severe hypokalemia and hypophosphatemia presenting with carpopedal spasm associated with rhabdomyolysis - Fainardi, Valentina; Cabassi, Aderville; Carano, Nicola; Rocco, Rossana; Fiaccadori, Enrico; Regolisti, Giuseppe; Dodi, Icilio; Del Rossi, Carmine (Acta Biomedica Atenei Parmensis, 2014)
Background Severe hypokalemia, defined as serum potassium < 2.5 mEq/L, may lead to neuromuscular, gastrointestinal, and ECG abnormalities. Neuromuscular consequences of hypokalemia include weakness, cramps, rarely paralysis, eventually progressing to rhabdomyolysis. Case presentation We report a case of a 4-year-old girl presenting carpopedal spasm and rhabdomyolysis due to severe hypokalemia associated to hypophosphatemia and hypovolemia. At one month of age she underwent an ileal resection because of a neonatal necrotizing enterocolitis, and a bowel resection at two years of age, because of sub-occlusive episodes. The child had frequent episodes of diarrhoea and was treated with oral white clay (kaolin) and a restrictive diet. Three days prior the admission to the hospital she had numerous episodes of watery diarrhoea. Laboratory tests revealed severe hypokalemia, hypophosphatemia, normal calcium levels associated with marked dehydration. An ECG demonstrated sinus bradycardia, ST-segment depression, T-wave flattening, U-wave, and long-QTc. Symmetric carpal and pedal spasms were observed. A marked rise of creatinine phosphokinase and myoglobin associated to cola colored urine was observed. Intravenous supplementation of potassium phosphate as well as adequate volume repletion led to an improvement of the clinical condition, to the disappearance of carpal and pedal spasms, to normalisation of ECG.  Conclusions Careful electrolytes and volume supplementation led to the correction of potential life-threatening arrhythmias and obtained a complete recovery from carpopedal spasm and rhabdomyolysis. Dietary restriction and pharmacological preparations as kaolin have to be administered with caution to treat diarrhea in children and particularly in those who may present other pre-existing risk factors.